2015
DOI: 10.1242/dev.120527
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathy proteins establish a bipartite signaling compartment in a C. elegans thermosensory neuron

Abstract: How signaling domains form is an important, yet largely unexplored question. Here, we show that ciliary proteins help establish two contiguous, yet distinct cyclic GMP (cGMP) signaling compartments in Caenorhabditis elegans thermosensory AFD neurons. One compartment, a bona fide cilium, is delineated by proteins associated with Bardet-Biedl syndrome (BBS), Meckel syndrome and nephronophthisis at its base, and requires NPHP-2 (known as inversin in mammals) to anchor a cGMP-gated ion channel within the proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…The AFD ending in young animals consists of a microtubule‐based cilium embedded in a nest of actin‐rich microvilli (Doroquez et al, 2014; Nguyen, Liou, Hall, & Leroux, 2014; Perkins et al, 1986) (Figure 4a). To test whether AFDs in aged animals undergo morphological changes, we used a number of cell‐specific fluorescent transgenes to examine AFD endings as well as dendrites (Figure 4b,c, and Table , Figure ,).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AFD ending in young animals consists of a microtubule‐based cilium embedded in a nest of actin‐rich microvilli (Doroquez et al, 2014; Nguyen, Liou, Hall, & Leroux, 2014; Perkins et al, 1986) (Figure 4a). To test whether AFDs in aged animals undergo morphological changes, we used a number of cell‐specific fluorescent transgenes to examine AFD endings as well as dendrites (Figure 4b,c, and Table , Figure ,).…”
Section: Resultsmentioning
confidence: 99%
“…The three guanylyl cyclases, GCY‐8, GCY‐18, and GCY‐23, fuel cyclic GMP that gates the TAX‐2/TAX‐4 cation channel required for thermosensation (Komatsu et al, 1996,1999). GCY‐8, GCY‐18, and GCY‐23 are localized to the actin‐rich microvilli, whereas TAX‐2 and TAX‐4 subunits are enriched in the cilium (Coburn & Bargmann, 1996; Inada et al, 2006; Komatsu et al, 1996; Nguyen et al, 2014). While missing one of the three guanylyl cyclases has minimal effects on AFD responses to thermal stimuli, elimination of all three abolishes AFD responses (Kuhara, Ohnishi, Shimowada, & Mori, 2011; Ramot, MacInnis, & Goodman, 2008; Takeishi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next tested whether rdl-1 was required in a different sensory neuron for enrichment of rGCs in the sensory cilium. GCY-8 is specifically expressed in thermosensory AFD neurons, and is highly enriched in their cilia (17,48). We found that GCY-8, like GCY-9, required rdl-1 to be enriched in sensory cilia (Fig.…”
Section: Rdl-1 Is Required For Trafficking Of Receptor-type Cyclase Fmentioning
confidence: 64%
“…Other mutations affect kinesinand dynein-dependent transport of cargo into and out of the cilium (i.e., intraflagellar transport) (15). Other genes encode proteins that localize to subcompartments of the cilium and define a complex macromolecular structure within the cilium (16)(17)(18).…”
mentioning
confidence: 99%